2012
DOI: 10.1002/art.34482
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and serologic comparison of African American and Caucasian patients with systemic sclerosis

Abstract: Objective Epidemiology studies suggest that Systemic Sclerosis is more common, occurs at a younger age and is more severe in African-Americans than Caucasians. However, the scleroderma autoantibody profile is very different between these two ethnic subgroups. This study examines the demographic and disease features, frequency and severity of internal organ system involvement and survival in African-American and Caucasian SSc patients with particular attention to their serum autoantibody profiles. Methods Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
121
9
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 22 publications
23
121
9
7
Order By: Relevance
“…In addition, McNearney et al, (37) reported that African American patients have a higher rate of ILD (46%) compared to White (19%) and Hispanic (25%) patients, as well as a more severe ILD as measured by pulmonary function tests (PFTs). Steen and colleagues (6) also reported a higher rate of ILD amongst African American patients (52%) compared to White patients (11%), particularly those that were ATA positive (44% in African American SSc patients versus 18%…”
Section: Overview Of Interstitial Lung Disease In Systemic Sclerosismentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, McNearney et al, (37) reported that African American patients have a higher rate of ILD (46%) compared to White (19%) and Hispanic (25%) patients, as well as a more severe ILD as measured by pulmonary function tests (PFTs). Steen and colleagues (6) also reported a higher rate of ILD amongst African American patients (52%) compared to White patients (11%), particularly those that were ATA positive (44% in African American SSc patients versus 18%…”
Section: Overview Of Interstitial Lung Disease In Systemic Sclerosismentioning
confidence: 93%
“…A more severe organ involvement is seen in those with dcSSc, compared to those with lcSSc. In Caucasian dominant populations such as in Europe and North America lcSSc is more common (56%) than dcSSc (34%) (5) , whereas in AfricanAmerican and Black populations the reverse is true, with rates of dcSSc of up to 82% being reported in Nigeria (6)(7)(8)(9) .…”
Section: Overview Of Systemic Sclerosismentioning
confidence: 99%
See 3 more Smart Citations